Changes in Body Weight, Glucose Homeostasis, Lipid Profiles, and Metabolic Syndrome after Restrictive Bariatric Surgery - To, V. T.; Hüttl, T. P.; Lang, R.; Piotrowski, K.; Parhofer, K. G. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Bariatric surgery is an established therapy for morbid obesity. We evaluated the effects of sleeve-gastrectomy on weight, glucose and lipid metabolism and prevalence of metabolic-syndrome for up to 2 years.In 52 morbidly obese patients weight, BMI, total-cholesterol, triglycerides, HDL-cholesterol, LDL-cholesterol, Lipoprotein(a), glucose, HbA1c, insulin, and criteria defining the metabolic-syndrome were determined preoperatively and 6 (n=52), 12 (n=41) and 24 (n=5) months after surgery.BMI decreased from 51±8 kg/m² to 40±7, 39±8, and 38±9 kg/m² at 6, 12, and 24 months postoperatively. Glucose and HbA1c changed from 116±44 to 93±21 and 94±18 mg/dl and 6.0±1.3 to 5.4±0.8 and 5.4±0.8% at 6 and 12 months postoperatively. Triglycerides decreased from 159±87 to 116±41 and 116±62 mg/dl, while HDL-cholesterol increased from 46±12 to 50±12 and 56±13 mg/dl at 6 and 12 months. None of the changes correlated with changes in weight. Prevalence of metabolic syndrome decreased from 81% to 36% and 34% at 6 and 12 months, with individual criteria (central obesity, triglycerides, HDL-cholesterol, hypertension, and fasting glucose) being reduced by 8/12%, 31/28%, 12/37%, 27/30%, and 38/31% at 6/12 months, respectively. The decrease in triglycerides and HbA1c was more pronounced in hypertriglyceridemic patients compared to normo-triglyceridemic patients, while there was no significant difference between diabetic and non-diabetic patients.This is the first study evaluating sleeve-gastrectomy in German patients. Our data indicate that sleeve-gastrectomy induces a similar metabolic improvement as malabsorptive surgery. Although metabolic improvement did not correlate with weight reduction, improvement almost exclusively occurred within the first 6 months, when significant weight reduction occurred. It is unclear whether this relates to the operative techniques or to the selection of patients.
Keywords: bariatric surgery; sleeve gastrectomy; diabetes; dyslipidemia; metabolic syndrome